2013
DOI: 10.1891/0886-6708.11-00151
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Social Support, Cognitive Appraisal, and Quality Health Care in Black Mothers’ Stress-Resilience Process Following Loss to Gun Violence

Abstract: Although much attention has been granted to the perpetrators and victims of gun violence, limitations exist in our understanding of the psychological well-being of parents grieving children lost to gun violence. The purpose of this study was to examine the mediating effects of social support, cognitive appraisal, and quality health care on the relationship between traumatic stress and resilience among Black mothers bereaving children to gun violence. A cross-sectional design and network sampling method were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
(67 reference statements)
0
32
0
2
Order By: Relevance
“…The nonsignificant but meaningful improvement in the Self‐Regulatory: Cognitive subscale of the WRI in the current study is consistent with wider research indicating that resilient responses to stressors involve adaptive cognitive appraisal and processing of situations (Bailey et al . ). This is an important finding that could be explored in future research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The nonsignificant but meaningful improvement in the Self‐Regulatory: Cognitive subscale of the WRI in the current study is consistent with wider research indicating that resilient responses to stressors involve adaptive cognitive appraisal and processing of situations (Bailey et al . ). This is an important finding that could be explored in future research.…”
Section: Discussionmentioning
confidence: 97%
“…This involves a series of protective factors and processes that support the restoration of well-being and performance (King & Rothstein 2010). The manner in which a person responds to stressors is influenced by their cognitive appraisal of situations and their capacity to process stressors, with the subsequent understanding and integration of stressors to their life (Bailey et al 2013). Resilience, therefore, encompasses both internal and external processes, resources, and characteristics that strengthen individuals' adaptive responses and outcomes from adverse events (McLarnon & Rothstein 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant psychosocial determinants in regards to the efficacy/health relationship include perceived stress, sense of control, social support and perceived standing in society [9], while fatalism is a key component of Bandura’s social cognitive theory relating to self-efficacy and health [10]. …”
Section: Introductionmentioning
confidence: 99%
“…As a result, Black mothers unduly suffer from gun violence loss and bear the social, emotional, and fi nancial burden of survivorship. Our research with Black mothers has shown that following the loss of children to gun violence they struggled with increased traumatic stress, diminished social and formal supports, and decreased access to psychological services and victims compensation (Bailey, Sharma, & Jubin, 2013 ;Bailey, Clarke, & Salami, 2015 ). Racism is of particular importance in Black mothers' grieving and resilience processes.…”
Section: Trauma and Gun Violence Lossmentioning
confidence: 99%
“…Given the scarcity of research focusing on Black women's experience with gun violence loss (Bailey, Sharma, & Jubin, 2013 ;Burke, Neimeyer, & McDevitt-Murphy, 2010 ), research that critically examines the dominant paradigms relevant to race, culture, and context that shape survivors' resilience experience is needed. Specifi cally, the post-homicide experiences of Black mothers, who are disproportionately affected by loss to gun violence, should be explored in light of service gaps and the need for improvements and informal supports to enhance the capacity of families and friends to provide ongoing support.…”
Section: Researchmentioning
confidence: 99%